Patrones socio-culturales de feminidad, comunicación mediática y representaciones de género en medios impresos orenses. - Crespo Carreño, Michelle Thalia; Cruz Sandoval, Angy Priscilla (Machala, 2020)
This research is motivated by the acts of gender violence that have occurred in the country, which, according to various studies, have triggered an infinity of deaths, abuse and exploitation in women. According to the report of a study carried out in Ecuador and presented in the article "Sociocultural factors that influence women victims of intrafamily violence" by the authors Illescas, Tapia and Flores, (2018), it is evidenced that 6 out of 10 women have been exposed to some type of violence, which is manifested by different factors and which puts women in a state of vulnerability, being thus sometimes because they suffer from low resources or have a low level of education, they are considered more likely to suffer from violence physical, verbal or psychological. These data, for the authors of the study, show that women have become an easy target for abuse, denigration and devaluation that is given to them in society; thus creating certain sociocultural patterns that define women throughout life and that are also "a source of machismo, of stereotypes that denigrate women as sexual objects, the feminine is less valued and it is legitimized in the service of the traditionally constructed masculine ”. (Illescas, Tapia and Flores, 2018). Which are also replicated by the media, which act as agents of socialization of the values, opinions, representations and stereotypes present in society. The mass media are capable of influencing and reinforcing stereotypical beliefs or contributing to the eradication of these. Apreza (2020, p.30) mentions that stereotypes towards women can be seen in the mass media as a parameter of what they should be. Women are linked to "affective activities aimed at caring for children, the home and the partner, as well as the possession of characteristics such as submission, self-denial and dependence". These superficial representations create prejudices, discrimination and a negative assessment of the roles that women have in society. Therefore, this work revolves around the study of the relationship between the sociocultural patterns on femininity existing in Orense citizenship, media communication and gender violence. In addition to identifying the media representations and attributes issued by the provincial print media about women and violence against them. For the development of the research work, a qualitative methodology was used based on the documentary-bibliographic review of partial works carried out within the framework of the research macro-project “Analysis of gender representations in printed newspapers and gender violence against women in the province of El Oro ”, where in the first instance and to cover the first objective set, we worked with information matrices collected in investigative degree works (Sánchez, 2019 and Valarezo, 2019), where journalistic notes starring women are analyzed and identifies sociocultural patterns, stereotypes, representations of gender-femininity and the agenda of attributes present in publications and provincial media communication. For the second objective of this research, data from opinion polls carried out in the cantons of Machala, El Guabo, Huaquillas and Santa Rosa and collected through degree works on the subject of sociocultural patterns, media communication and gender violence were consolidated ( Armijos V., 2018; Gonzalez A., 2019 and Armijos E., 2019) and opinion polls carried out by the research group through the subjects of Public Opinion and Statistics. In the third objective, the consolidation and analysis of interviews on the same topic was carried out with 10 journalism specialists from the printed newspapers that are the object of the investigation and 7 specialists in social areas, collected in degree works and complex examinations developed within the framework of the same topic of the project, corresponding to the authors: Matamoros (2018) Telcan (2018), Sanchez (2019), Valarezo (2019), Romero (2019), Moreno (2019), Díaz (2019), Villamar (2019). The results of this research show that in the articles carried out by women that appear in the provincial printed media with the greatest circulation, publications that transmit macho sociocultural patterns predominate and that continue to generate stereotypes and unfavorable representations of the role that women play today in the society and that are directly related to the prevailing climate of gender violence. On the other hand, in opinion polls it is evident that women have positioned an image of an independent human being, however the egalitarian condition in front of men, despite being present in the social imaginary, appears timidly in the results, which suggests a resistance to the still prevailing macho pattern. In relation to violence against women, the machismo of men is still recognized as the main cause as they are considered more important than women themselves.
La presente investigación se motiva a raíz de los hechos de violencia de género suscitados en el país, los cuales, según diversos estudios, han desencadenado, una infinidad de muertes, abuso y explotación en las mujeres. De acuerdo al reporte de un estudio efectuado en Ecuador y presentado en el artículo “Factores socioculturales que influyen en mujeres víctimas de violencia intrafamiliar” de los autores Illescas, Tapia y Flores, (2018), se evidencia que 6 de cada 10 mujeres han sido expuestas a algún tipo de violencia, que se manifiesta por distintos factores y que ponen a la mujer en un estado de vulnerabilidad siendo así que algunas veces por sufrir de bajos recursos o tener un nivel de educación bajo, son consideras más propensas a padecer de violencia física, verbal o psicológica. Estos datos, para los autores del estudio, evidencian que las mujeres se han convertido en un blanco fácil para el abuso, denigración y desvalorización que se le da en la sociedad; creando así ciertos patrones socioculturales que van definiendo a la mujer a lo largo de la vida y que también son “fuente del machismo, de estereotipos que denigran a la mujer como objeto sexual, se valora menos a lo femenino y se legitima éste al servicio de lo masculino tradicionalmente construido”. ( Illescas, Tapia y Flores, 2018). Los cuales son también replicados por los los medios de comunicación, que actúan como agentes de socialización de los valores, opiniones, representaciones y estereotipos presentes en la sociedad. Los medios masivos son capaces de influir y reforzar creencias estereotipadas o contribuir a la erradicación de estos. Apreza (2020, p.30) menciona que en los medios masivos se puede visualizar los estereotipos hacia las féminas como parámetro de lo que deben ser ellas. A las mujeres se las vincula a “las actividades afectivas encaminadas al cuidado de los hijos, del hogar y de la pareja, así como a la posesión de características tales como la sumisión, la abnegación y la dependencia”, estas representaciones superficiales crean prejuicios, discriminación y una valoración negativa sobre roles que tienen las mujeres en la sociedad. Por ello, el presente trabajo gira en torno al estudio de la relación entre los patrones socioculturales sobre feminidad existentes en la ciudadanía orense, la comunicación mediática y la violencia de Género. Además de identificar las representaciones mediáticas y atributos que emiten los medios impresos provinciales sobre la mujer y la violencia hacia las mismas. Para el desarrollo del trabajo investigativo se utilizó una metodología de naturaleza cualitativa en base a la revisión documental-bibliográfica de trabajos parciales realizados en el marco del macroproyecto de investigación “Análisis de representaciones de género en diarios impresos y violencia de género contra las mujeres en la provincia de El Oro”, donde en primera instancia y para cubrir el primer objetivo planteado, se trabajó con matrices de información levantadas en trabajos investigativos de titulación (Sánchez, 2019 y Valarezo, 2019), donde se analizar notas periodísticas protagonizadas por mujeres y se identifica patrones socioculturales, estereotipos, representaciones de género-feminidad y agenda de atributos presentes en las publicaciones y la comunicación mediática provincial. Para el segundo objetivo de esta investigación se consolidaron datos de sondeos de opinión realizados en los cantones de Machala, El Guabo, Huaquillas y Santa Rosa y levantados a través de trabajos de titulación sobre la temática de patrones socioculturales, comunicación mediática y violencia de género (Armijos V., 2018; Gonzalez A., 2019 y Armijos E., 2019) y sondeos de opinión levantados por el grupo de investigación a través de las asignaturas de Opinión Pública y Estadística. En el tercer objetivo, se realizó la consolidación y análisis de entrevistas sobre el mismo tema a 10 especialistas de periodismo de los diarios impresos objeto de la investigación y 7 especialistas en áreas sociales, levantadas en trabajos de titulación y exámenes complexivos desarrollados en el marco del mismo tema del proyecto, correspondientes a los autores: Matamoros (2018) Telcan (2018), Sanchez (2019), Valarezo (2019), Romero (2019), Moreno (2019), Díaz (2019), Villamar (2019). Los resultados de esta investigación evidencian que en las notas protagonizadas por mujeres que aparecen en los medios impresos provinciales de mayor circulación, predominan publicaciones que transmiten patrones socioculturales machistas y que continúan generando estereotipos y representaciones desfavorables del rol que la mujer desempeña hoy en día en la sociedad y que están directamente relacionadas con el clima de violencia de género que predomina. Por otro lado, en los sondeos de opinión se evidencia que la mujer ha posicionado una imagen de ser humano independiente, sin embargo la condición igualitaria frente al hombre a pesar de estar presente en el imaginario social, aparece tímidamente en los resultados lo cual deja entrever una resistencia frente al patrón machista aún predominante. En relación con la violencia hacia la mujer aún se reconoce al machismo de los hombres como la causa principal al éstos considerarse más importantes que las propias mujeres.
Keywords: PATRON SOCIOCULTURAL; ESTEREOTIPO; VIOLENCIA; GENERO